Acyclic nucleoside phosphonates with 5-azacytosine base moiety substituted in C-6 position - Krecmerová, Marcela; Masojídková, Milena; Holý, Antonín (Bioorganic & medicinal chemistry, 2010)
Two methods for preparation of 6-substituted derivatives of anti DNA-viral agent 1-(S)-[3-hydroxy-2-(phosphonomethoxy)propyl]-5-azacytosine (HPMP-5-azaC) were developed: (1) ammonia mediated ring-opening reaction of diisopropyl esters of HPMP-5-azaC (4) to carbamoylguanidine derivatives followed by ring-closure reaction with orthoesters and (2) condensation reaction of 6-substituted 5-azacytosines with diisopropyl (1S)-[2-hydroxy-1-tosyloxymethyl)ethoxy]methylphosphonate (15). Deprotection of diisopropyl esters to free phosphonic acids was performed with bromotrimethylsilane in acetonitrile followed by hydrolysis. In contrast to parent compound HPMP-5-azaC, a substantial decrease of antiviral activity in case of 6-substituted analogues occurred. Surprisingly, N-3 isomer of 6-methyl-HPMP-5-azaC in the form of isopropyl ester revealed activity against RNA viruses (Sindbis virus).
Keywords: virové nemoci; Animals; Antiviral Agents; Viruses; Chlorocebus aethiops; cytosin; buněčné linie; antivirové látky; Vero Cells; Nucleosides; viry; Cytosine; lidé; Vero buňky; nukleosidy; Cell Line; Virus Diseases; organofosfonáty; Cercopithecus aethiops; zvířata; Organophosphonates; Humans